Percutaneous endoscopic spinal surgery for lumbar disc prolapse in Erbil city of Iraq: A study on 60 patients - Hammood, Emad Kh (Diyala Journal of Medicine, 2018)
Background: As an alternative to back surgeries, endoscopic spinal operations is the most effective and safe procedure that does not impose the fear reaction to the patients. Objective: In this study the results, complications, and outcomes of 60 patients complaining from prolapsed lumbar inter-vertebral discs who experienced prolapsed endoscopic lumbar discectomy (PELD) were reported. Patients and Methods: This is a prospective study conducted in three sentinel hospitals over a period of 3 years (2013-2015) in Erbil city of Iraq. Clinical findings in addition to pre-operative MRI were the main diagnostic methods used for including patients who were suffering from lumbar disc herniation at different levels. Clinical appraisal was done utilizing the modified Macnab criteria. The Storz lens spinoscope was utilized to perform PELD. Results: Sixty patients (37 males and 23 females) with lumbar disc herniation were included in the study. The mean operative time was 50 minutes. Patients were discharged during 1st 24 hours post-operatively. After surgery, patients were followed up for two months to three years with a mean of 18 months. Seven (11.7%) patients developed complications including one (1.7%) instance of shallow nerve injury, three (5%) with dural tears, two (3.3%) instances of intermittent delayed disc prolapse and one patient (1.7%) had post-operative discitis. Modified Macnab criteria (excluding patients with long dural tear) showed excellence results for 36 patients, while good results were observed for 17 patients, reasonable results for 3 patients and poor results for 2 patients. The achievement rate was 91.4% . Conclusion:Although endoscopic spinal discectomy is a compelling procedure for management of lumbar disc prolapse, and although its final outcome is reasonable it is not devoid from complications.